The Demographical Analysis of Indonesian Young Adults' Financial Anxiety - Abbya Pratiwi Ramadhani; Taufik Faturohman (UNIVED Press, 2024)
This study aims to understand what causes financial anxiety among Indonesian Young Adults in terms of demographical. A survey from 400 respondents was collected through an online questionnaire from July to August 2023 and analyzed using descriptive statistics, and continued by using Kruksal Wallis and Mann Whitney U to test whether there is a statistically significant difference between two or more independent variables. The result of this study found that there are no significant differences in gender and income in financial anxiety, but there are significant differences in educational level and occupation in financial anxiety. Individuals with only a high school degree as their educational background, and unemployed individuals have higher levels of financial anxiety than other groups.